Analisis Faktor Yang Mempengaruhi Penerimaan Mahasiswa Terhadap QRIS Menggunakan Technology Acceptance Model (TAM) - sri, Sri Indriani; Adam Bachtiar; Indriaturrahmi; Akbar Juliansyah (Infotek: Jurnal Informatika dan Teknologi, 2024)
This study aims to analyze what factors influence student acceptance of QRIS at Mandalika Education University using the Technology Acceptance Model (TAM) as the basis for the research model. The factors analyzed include perceived ease of use, perceived usefulness, attitude toward using, behavioral intention to use, and actual system use. The research method used is quantitative method by distributing questionnaires to Mandalika Education University students. Respondents who were sampled in this study amounted to 120 respondents with criteria that have been determined by the author with technical random sampling Data collection using a 5 Likert scale questionnaire method The data collected were analyzed using Structural Equation Modeling (SEM) with the help of AMOS software. The results showed that perceived ease of use has a significant effect on perceived usefulness, attitude towards using has a significant effect on behavioral intention to use, behavioral intention to use has a significant effect on actual system use